Search for genetic predictors of acute coronary syndrome in patients after coronavirus disease 2019 - V. A. Kozik; L. A. Shpagina; I. S. Shpagin; S. V. Minnikh; N. G. Lozhkina; V. N. Maksimov (Российский кардиологический журнал, 2024)
Aim. To assess the rs2285666 nucleotide sequence of the angiotensin-converting enzyme 2 (ACE2) gene and its association with acute coronary syndrome (ACS) in patients after coronavirus disease 2019 (COVID-19).Material and methods. The study included 100 patients after COVID-19, including 50 men and 50 women, hospitalized with a diagnosis of ACS. The diagnosis of COVID-19 in all 100 patients was confirmed by a positive polymerase chain reaction (PCR) smear. All patients underwent percutaneous transluminal coronary angioplasty with stenting, standard clinical and paraclinical examination, and genetic testing of the rs2285666 ACE2 gene by PCR followed by restriction fragment length polymorphism analysis. The comparison group consisted of 200 patients with ACS after COVID-19, confirmed by a PCR smear or antibody titer.Results. Statistically significant differences were obtained for the AA genotype, carriage of which among male patients with ACS after COVID-19 was 2,5 times less common than in men in the control group (OR =0,391, 95% CI: 0,167-0,917; p=0,028). On the other hand, carriage of the rs2285666 GA genotype of the ACE2 gene is not associated with an increased risk of ACS in women after COVID-19. There were no significant differences in genotype frequencies in the group of women and in the general group (without division by sex).Conclusion. The data obtained may indicate a protective role of the rs2285666 AA genotype of the ACE2 gene for males regarding ACS development after COVID-19. These results are the first steps towards building a prognostic model to estimate the ACS risk in patients after COVID-19, which will reduce morbidity and mortality for this group of patients.